The causality between gut microbiota and non-Hodgkin lymphoma: a two-sample bidirectional Mendelian randomization study - Fu, Jinjie; Hao, Zheng (Frontiers in Microbiology, 2024)
Background: Studies have indicated an association between gut microbiota (GM) and non-Hodgkin lymphoma (NHL). However, the causality between GM and NHL remains unclear. This study aims to investigate the causality between GM and NHL using Mendelian randomization (MR).Methods: Data on GM is sourced from the MiBioGen consortium, while data on NHL and its subtypes is sourced from the FinnGen consortium R10 version. Inverse variance weighted (IVW) was employed for the primary MR analysis method, with methods such as Bayesian weighted Mendelian randomisation (BWMR) as an adjunct. Sensitivity analyses were conducted using Cochran's Q test, MR-Egger regression, MR-PRESSO, and the "Leave-one-out" method.The MR results showed that there is a causality between 27 GMs and NHL. Among them, 20 were negatively associated (OR < 1), and 7 were positively associated (OR > 1) with the corresponding diseases. All 27 MR results passed sensitivity tests, and there was no reverse causal association.By demonstrating a causal link between GM and NHL, this research offers novel ideas to prevent, monitor, and cure NHL later.